Frequency of Infra Orbital Nerve Recovery after Open Reduction Internal Fixation of Zygomatico Maxillary Fracture - Hina Jabeen, Tariq Sardar, Erum Riaz, Ashfaq Ahmed, Asfandyar Luni, Hafiz Mujtaba Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current research aimed to assess the repossession frequency of infraorbital nerve paresthesia after open reduction internal fixation in the treatment of ZMC fractures. Methodology: Randomized control trial was conducted in department of Oral and Maxillofacial Surgery, Ziauddin hospital and Medical University, Karachi from Jan 2020 to July 2021. Data was collected after ethical approval. Patients with unilateral zygomatico maxillary bone fracture satisfying the exclusion and inclusion criteria, and who were ready to give knowledgeable approval after the given explanation about study procedure, how data taken from their cases will be used for research purpose, and after discussion on risk as well as benefits of the procedure, were involved in our study. Results: Data of 150 patients were collected. Out of these 150, 82 were and females 68 were male. The mean age (SD) was 31.48 (5.67 SD) years. Other socio-demographic characteristics are represented in table 1. 106 (71%) of ZMC patients recovered from infra orbital nerve after Open Reduction Conclusions: On the basis of this study it is recommended that open reduction as chosen mode of management whose outcomes in enhanced recovery of functional nerve amongst paresthesia patients after linked to closed reduction approaches. Keywords: Infra Orbital Nerve, Zygomatico Maxillary Complex (ZMC)